EXPLORING THE MENTAL ISSUE IN HUMAN BEINGS: A MORAL PERSPECTIVE IN “MEDUSA” BY JESSIE BURTON - Fauzi, Resti Hadiyanti; Pratiwi, Dyani Prades (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2025)
Mental health is a state of well-being that enables individuals to cope with stress, realize potential, learn, work well, and contribute to the community. Jessie Burton's novel